ENSURING EFFECTIVE EMPLOYMENT OF CATEGORIES OF THE POPULATION IN NEED OF SOCIAL PROTECTION (American Journal of Research in Humanities and Social Sciences, 2025)
As a result of socio-economic reforms carried out in our republic, fundamental changes are being implemented in all areas. Opinions were given about the work being carried out to organize social protection at the neighborhood level, to provide social services and assistance based on a comprehensive approach, to prevent the population from falling into a severe social situation, as well as to increase the addressability and effectiveness of social protection and to ensure the socialization of the population in need of assistance.